MYC Gene Rearrangements Are Closely Associated with Poor Survival of Diffuse Large B Cell Lymphoma with Hepatitis B Virus Infection - Liu, Zhihe (Biomed Res Int, 2017)
The aim of this study was to identify clinical adverse prognostic factors affecting overall survival (OS) of diffuse large B cell (DLBCL) patients with hepatitis B virus (HBV) infection. In this study, 30 DLBCL patients with HBV infection and 51 DLBCL patients with HBV-free were reviewed retrospectively. As of July 2016, the median follow-up period was 26.4 months (3.0~65.0 months). The median OS of patients in HBV infection group was 38.6 months, while that of patients in HBV-free group was not reached (P = 0.042); the median progression-free survival (PFS) of patients in HBV infection group was worse than that in HBV-free group, 18.5 months and 38.5 months (P = 0.118), respectively. The rate of MYC and BCL2 gene rearrangements in HBV infection group was significantly higher than that in HBV-free group, 20.0% versus 3.9% (P = 0.019) and 23.3% versus 5.9% (P = 0.021), respectively. Multivariable analysis indicated that IPI (P = 0.002), chemotherapy regimens (P = 0.017), and MYC gene rearrangements (P = 0.004) were independent adverse prognostic factors for all DLBCL patients in this study. Results demonstrated that the poor survival of DLBCL patients with HBV infection was closely involved in chemotherapy regimens, IPI, and MYC gene rearrangements.